Prevalence of overweight And Obesity in Canadian Children: A Decade of Progress in the Canadian Community Health and Health Measure Surveys. (1st June 2016) - Rodd, C; Sharma, A
Abstract: BACKGROUND: Previous studies using the Canadian Community Health Survey (CCHS) demonstrated an increase in the prevalence of overweight or obesity in Canadian children from 23.3% to 34.7% (1978– 2004) using the new 2010 WHO for Canada Growth Charts. OBJECTIVES: To better define temporal trends in overweight and obesity status, this study examines additional data from the Canadian Health Measures Survey (CHMS, 2009-2013) by applying current Canadian definitions based on WHO body mass index (BMI) thresholds and recently validated waist-circumference norms from NHANES III (1988-1994). Associations with variables such as family income, parent education and number of parents were also explored over this time frame. DESIGN/METHODS: Directly measured heights and weights were available for 14, 014 children aged 3-19y from the decade 2004 to2013 in CCHS (n=8976)CHMS cycle 2 (n=2578) and CHMS cycle 3 (n= 2460). Z-scores for BMI, height, and weight were based on the 2014 WHO Growth Charts for Canada, including their new extension of weight-for-age beyond 10y. For waist circumference and waist-height ratios, we used new charts from the NHANES III reference population. Inverse probability survey weights were used to account for non-response and under-coverage. RESULTS: The sex distribution was similar in each survey cycle and 80% were of white race/ethnicity. Using current WHO definitions based on BMI, we observed a decline in the proportion 'overweight or obese' from 30.7% (95%CI=29.4–32.0) to 27.0% (25.7–28.3, p<0.001) and a stabilizations in obesity rates at 13%. Rates of overweight and obesity were higher in boys, non-whites, and older children. These trends persisted after regression adjustment for age, gender, and race-ethnicity. Although declining, median Z-scores for BMI, weight, and height were positive compared to the WHO reference population. Waist-circumference and waist-height ratio Z-scores were negative, with less central adiposity than American children in historic or contemporary NHANES cohorts. Temporal trends in overweight/obesity appear to vary with family income, educational achievement, and immigrant status. CONCLUSION: After a period of dramatic growth, both BMI-Z-scores and the prevalence of overweight or obesity appear to be declining in in Canadian children, attesting to progress against this important public health challenge.